B. Axford - G.K. Browning - R. Huggins - B. Rosamond - J. Turner ., Politics: An Introduction, Routledge, Λονδίνο 1997, 532 σελ. A. Heywood , Politics, Macmillan, Λονδίνο 1997,431 σελ. - Γεωργαντάς, Ηλίας (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
Δεν διατίθεται περίληψη.